PENGARUH INSENTIF FINANSIAL DAN NON FINANSIAL TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Distro Resist Wear Turen Malang) - Yusvita Pavita Syamsudin; Abdul Qodir Djaelani; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTThis research aims to know the influence of performance area the effect of Financial Incentives and Non-Financial Incentives to Employee Performance with Motivation as intervening variable in Resist Wear Distro Turen Malang.This research is Explanatory Research. The research data of performance area, Incentives of Financial and Non Financial on Employee Performance with Motivation as intervening variable, obtained from Resist Wear Distro Turen Malang. Population in this research is all employees of Resist Wear Distro Turen Malang. Data collection are using questionnaire data. Then, the data analysis used instrument test, normalitas test, classis assumption, and hypothesis test. Based on the finding of this research, it can be concluded that the partiallly financial incentive variable has significant effect on employee performance, non financial incentive has no significant effect on employee performance, motivation has significant effect on employee performance, motivation mediates partially the relationship between financial incentive on employee performance, Motivation perfectly mediates the relationship between non financial incentives on a performance. Keywords: Financial Incentives, Non Financial Incentives, Employee Motivation and Performance.